Community participation in coastal resource management the role of Igdanlog Fisherfolks' Association in the Kalaparan coral reef protected area, Tobias Fornier, Antique - Fernandez, Josen L.
This study focuse on the role of Igdanlog Fisherfolks' Association in the management and conservation of the Kalaparan Coral Reef Protected Area in Igdanlog, Tobias Fornier, Antique. Data for this study were gathered through Key Informant Interviews, Focus Group Discussion, and review of secondary data. These data were analyzed using the following conceptual and analytical tools: CBCRM as practiced in the Philippines, Stakeholder's Analysis, and the Modified Ladder of Community Participation. It was found out that the IFA was unable to meet some of the components of CBCRM such as capability building and sustainable livelihood which affected their attitude towards the management of their MPA. Key Stakeholders identified were the local government unit, Igdanlog Fisherfolks' Association and the fisherfolks. Community participation was classified as tokenism using the modified ladder of citizen's participation. This study concludes that in order to properly manage the KCRPA, the IFA should strengthen their commitment to change, start taking initiatives on how to improve their MPA, and stop depending on the LGU. Keywords: community-based coastal resource management, community participation, marine protected area
Research, Undergraduate, UPV Miag-ao, Bachelor of Arts (Community Development)
Keywords: Coastal resources; Coastal resources management .; Marine -protected-areas.